Identification of a membrane protein induced concurrently with cell filamentation by cyclic AMP in an Escherichia coli K-12 fic mutant. - Utsumi, R (1983)
A membrane protein with a molecular weight of 40,000 (40K protein) was induced concurrently with cell filamentation by cyclic AMP (cAMP) in a fic mutant. In the crp mutant and the wild-type strain, cell filamentation by cAMP was not observed, and the 40K protein was not induced. Induction of the 40K protein is regulated by the cAMP-cAMP receptor protein complex and is closely related to cell filamentation by cAMP in the fic mutant.